Association between coffee consumption and risk of renal cell carcinoma: a meta‐analysis. Issue 12 (10th December 2017) - Wijarnpreecha, Karn; Thongprayoon, Charat; Thamcharoen, Natanong; Panjawatanan, Panadeekarn; Cheungpasitporn, Wisit
Abstract: Background/Objectives: The risk of renal cell carcinoma (RCC) in individuals who regularly drink coffee is controversial. Several antioxidant compounds in coffee have been proposed to reduce the risk of RCC, while the findings from several studies raise concerns regarding a potential increased risk of RCC with coffee consumption. Aim: This meta‐analysis aims to evaluate the association between coffee consumption and RCC. Methods: A literature search was performed using MEDLINE, EMBASE and Cochrane Database of Systematic Reviews from inception until December 2016. Studies that reported odd ratios or hazard ratios comparing the risk of RCC in individuals who consumed a significant amount of coffee (at least one cup of coffee per day) versus those who did not consume coffee were included. Pooled risk ratios (RR) and 95% confidence intervals (CI) were computed using a random‐effect, generic inverse variance method. Results: Twenty‐two observational studies (16 case–control and 6 cohort studies) were included in our analysis to assess the association between RCC and coffee consumption. The pooled RR of RCC in individuals consuming coffee was 0.99 (95% CI, 0.89–1.11). Subgroup analyses stratified by gender showed pooled RRs of RCC of 1.15 (95% CI, 0.85–1.55) in females and 0.87 (95% CI, 0.72–1.04) in males. Conclusions: Our study demonstrates no significant association between coffee consumption and RCC. Thus, coffee consumption is likely not a risk factor for RCC. Whether coffee consumption has a potential role in reduced risk of RCC, particularly in men, requires further investigations.